ENSURING EFFECTIVE TEACHING, LEARNING AND ASSESSMENT IN HIGHER EDUCATION BASED ON THE RESULTS-BASED PARADIGM IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Паламарчук, Ольга (Modern engineering and innovative technologies, 2024)
The relevance of the study is evidenced by a number of documents of the European Higher Education Area. The theoretical foundations for ensuring effective teaching, learning and assessment in higher education based on an effective paradigm in the context